2023
DOI: 10.1039/d3tc03097k
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency enhancement of dopant-free perovskite solar cells by employing fluoro-substituted electron donor–electron acceptor type polymeric hole-transporting materials

Yunxiang Chen,
Xuelin Wang,
Guofeng You
et al.

Abstract: For the conventional n-i-p perovskite solar cells (PVSCs), dopant-free hole-transporting polymers can be employed to achieve high device performances. Herein, two electron donor-electron acceptor (D-A) type conjugated polymers PBCz-BTz and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…9,10 Therefore, HTMs should possess a well-aligned highest occupied molecular orbital (HOMO) with the valence band of the perovskite, high intrinsic charge mobility, and the ability to form high-quality coverage of the perovskite absorber. Recent studies have demonstrated the great potential of benzodithiophene (BDT)-based conjugated small molecules 11,12 and polymers 13,14 as HTMs due to several attractive features of the BDT unit. The rigid and planar BDT building block with two-dimensionally expanded π-systems enables tight stacking of molecules, which is favorable for achieving high charge mobility.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Therefore, HTMs should possess a well-aligned highest occupied molecular orbital (HOMO) with the valence band of the perovskite, high intrinsic charge mobility, and the ability to form high-quality coverage of the perovskite absorber. Recent studies have demonstrated the great potential of benzodithiophene (BDT)-based conjugated small molecules 11,12 and polymers 13,14 as HTMs due to several attractive features of the BDT unit. The rigid and planar BDT building block with two-dimensionally expanded π-systems enables tight stacking of molecules, which is favorable for achieving high charge mobility.…”
Section: Introductionmentioning
confidence: 99%